Kratom (Mitragyna speciosa)-Induced Hepatitis. Issue 4 (7th April 2022) - Allison, Devin R.; Mubarak, Muhammad; Sharma, Neal; Rao, Deepthi S.
ABSTRACT: Kratom is a plant with opioid-like properties known to produce stimulant and analgesic effects. Although there are numerous studies on the psychoactive components of kratom, less is known about the toxicity. Specifically, few reports describe kratom-induced hepatotoxicity and demonstrate histological features. We provide a case report detailing the clinicopathologic findings of drug-induced liver injury caused by kratom. The laboratory workup included significant elevation of total bilirubin and alkaline phosphatase. Liver biopsy demonstrated a prominent canalicular cholestatic pattern, mixed portal inflammation, and newly described perivenular necrosis. This report provides additional information on kratom toxicity because its use continues to rise.